Représentations et vécus d’enfants autour de la famille à Cotonou (Bénin) - Bénédicte Gastineau; Agnès Adjamagbo (Espace populations sociétés, 2022)
This paper focuses on family representations in Cotonou, Benin’s economic capital, based on drawings made by pupils of two primary schools located in contrasted socio-economic neighbourhoods. This innovative approach in demography accounts for how children symbolically think about the family in which they evolve on a daily basis, but also the one in which they project themselves in their future life, as adults. The drawings are not analysed as a reflection of social realities but as an expression of norms (in this case family norms) and their plasticity in time and space. They underline the dominant family patterns and show their variations according to socio-economic background. Beyond the differences, irrespective of their social origin, children's graphic productions reflect their passion for ways of life inspired by urban elites which are characterized by financial and material success. The analysis of these drawings collected in 2012 enables to explore the patterns of family transmission and reproduction. In this globalized society, vectors of norms and values are multiple and consist into opportunities for normative breaks.